2010
DOI: 10.3109/10428191003774960
|View full text |Cite
|
Sign up to set email alerts
|

The associations of Janus kinase-2 (JAK2) A830G polymorphism and the treatment outcomes in patients with acute myeloid leukemia

Abstract: The Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway is active in both normal hematopoiesis and hematological malignancies. Moreover, Janus kinase-2 (JAK2) is the key hematopoietic kinase, and mutations together with single nucleotide polymorphisms (SNPs) of JAK2 have been thoroughly evaluated. In this study, we aimed to investigate whether the synonymous genetic polymorphism A830G in the JAK2 gene is associated with the treatment outcomes of Ara-C-based chemotherapy regimens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[21][22][23] Single nucleotide polymorphisms of genes involved in hematopoietic signal-transduction were investigated less frequently. 24,25 In this study, we report an association of the JAK2 46/1 haplotype with disease characteristics and treatment out- 26,27 Retrieving haplotype information from the HapMap Project on rs12343867 and rs2230724 in a Chinese population revealed that the above polymorphisms are not in complete linkage (estimated haplotype frequencies of rs12343867/rs2230724: T/G: 57%, C/A: 23%, T/A: 18%, C/G: 2%, D': 0.892; P<0.000). 28 In Chinese AML patients, the AA genotype of rs2230724 was significantly associated with higher complete remission rate, and the GG genotype with early death.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Single nucleotide polymorphisms of genes involved in hematopoietic signal-transduction were investigated less frequently. 24,25 In this study, we report an association of the JAK2 46/1 haplotype with disease characteristics and treatment out- 26,27 Retrieving haplotype information from the HapMap Project on rs12343867 and rs2230724 in a Chinese population revealed that the above polymorphisms are not in complete linkage (estimated haplotype frequencies of rs12343867/rs2230724: T/G: 57%, C/A: 23%, T/A: 18%, C/G: 2%, D': 0.892; P<0.000). 28 In Chinese AML patients, the AA genotype of rs2230724 was significantly associated with higher complete remission rate, and the GG genotype with early death.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK is the gatekeeper in the JAK-STAT pathway, which is a major suppressor of some cytokines during cell-signaling process. The JAK/STAT pathway is active in human malignancies (Zhong et al, 2010). Aberrant activation of the JAK/STAT pathway may predispose to malignancy because of deregulation of proliferation, differentiation, or apoptosis (Vaclavicek et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…JAK gene polymorphisms were related with the susceptibility to disease activities for individual diseases. JAK mutations or SNPs are associated with leukemia (Zhong et al, 2010). The JAK SNP is part of a haplotype associated with enhanced susceptibility to myeloproliferative neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations